New Model of Integrated Care for Patients with Immune-Mediated Inflammatory Diseases - Esther Chamorro-de-Vega; C. M. González; L. Menchén; O. Baniandrés; A. Herranz; C. Lobo-Rodríguez; R. Romero-Jiménez; A. Ais-Larisgoitia; E. Lobato-Matilla; A. López-Esteban; A. López-Calleja; I. Marín-Jiménez; et al. (International Journal of Integrated Care)
Introduction: The complexity and transversality of the care for patients with immune-mediated inflammatory diseases (IMIDs) represents a challenge for the usual structure of health care services and requires a transformation of existing clinical management models. We describe the design, implementation and evaluation of a new collaborative care model for patients with IMIDs. Description: A group of multidisciplinary professionals including specialists from the rheumatology, gastroenterology, dermatology and pharmacy services designed and implemented an innovative health care model for patients with IMIDs that has changed the traditional model of care. One of the main challenges is the transversal leadership system in collaboration with all the hospital services involved, including the Medical Directorate of the hospital and patients, which promotes greater responsibility and empowerment. Discussion: Although IMID patient care by a multidisciplinary team is widely recommended, guidelines for IMID-specific models are lacking and few authors have reported controversial results of this strategy. Conclusions: CEIMI is a pioneering collaborative and multidisciplinary care model for patients with immune-mediated inflammatory diseases. This new model is integrated by physicians, pharmacists and specialised nurses and is oriented to meet the needs and expectations of the patients.